Implementasi Sistem Internet of Things (IoT) pada PT XXX menggunakan sistem MQTT - Sumartono, Katherine Febrianty; Samuel, Yusran Timur (TeIKa, 2024)
The Internet of Things (IoT) system has been implemented at PT XXX to improve operational efficiency, especially in monitoring the Ingersoll C1000 centrifugal compressor. This compressor produces high-pressure air that plays an important role in the nickel processing process. This system integrates the Message Queuing Telemetry Transport (MQTT) protocol, IoT sensors, Teltonika RUT951 gateway, and Mosquitto broker to send temperature data in JSON format in real-time. This data is then visualized using AVEVA PI Vision, which provides trend-based information to support analysis and decision making. Previously, monitoring was only carried out locally without historical data, making it difficult to detect potential damage. Operators also had to conduct direct inspections to the field to check the condition of the compressor, which was time-consuming and inefficient. With this IoT-based system, data can be monitored directly from the head office, saving travel time and increasing operational productivity. Trials in a real operational environment showed that data transmission via MQTT was stable even in a limited network. Visualization in AVEVA PI Vision provides a real-time picture that supports early detection of anomalies and data-driven decision making. The results of this study indicate that IoT technology with the MQTT protocol is able to improve monitoring efficiency, optimize system performance, and provide innovative solutions to connectivity challenges in the industry. This implementation also opens up new opportunities for IoT applications in supporting operational efficiency and sustainability.